Genome-wide meta-analysis of ascertainment and symptom structures of major depression in case-enriched and community cohorts - Adams, Mark J.; Thorp, Jackson G.; Jermy, Bradley S.; Kwong, Alex S. F.; Kõiv, Kadri; Grotzinger, Andrew D.; Nivard, Michel G.; Marshall, Sally; Milaneschi, Yuri; Baune, Bernhard T.; Müller-Myhsok, Bertram; Penninx, Brenda W. J. H.; et al. (Psychological medicine, 2024)
BackgroundDiagnostic criteria for major depressive disorder allow for heterogeneous symptom profiles but genetic analysis of major depressive symptoms has the potential to identify clinical and etiological subtypes. There are several challenges to integrating symptom data from genetically informative cohorts, such as sample size differences between clinical and community cohorts and various patterns of missing data.MethodsWe conducted genome-wide association studies of major depressive symptoms in three cohorts that were enriched for participants with a diagnosis of depression (Psychiatric Genomics Consortium, Australian Genetics of Depression Study, Generation Scotland) and three community cohorts who were not recruited on the basis of diagnosis (Avon Longitudinal Study of Parents and Children, Estonian Biobank, and UK Biobank). We fit a series of confirmatory factor models with factors that accounted for how symptom data was sampled and then compared alternative models with different symptom factors.ResultsThe best fitting model had a distinct factor for Appetite/Weight symptoms and an additional measurement factor that accounted for the skip-structure in community cohorts (use of Depression and Anhedonia as gating symptoms).ConclusionThe results show the importance of assessing the directionality of symptoms (such as hypersomnia versus insomnia) and of accounting for study and measurement design when meta-analyzing genetic association data.
Gesehen am 07.01.2025